PEMANFAATAN LIMBAH PLASTIK SEBAGAI MEDIA PEMBELAJARAN IPAS TENTANG SISTEM PEREDARAN DARAH PADA SISWA KELAS V MI. MUHAMMADIYAH ROMANG LOMPOA - Haerana; Daroe Iswatiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to address the difficulty of understanding the abstract concept of the Circulatory System among fifth-grade elementary school students and simultaneously contribute to solving the problem of plastic waste management through innovative learning media. The study employed the ADDIE Model Research and Development (R&D) method with a One Group Pretest-Posttest design. The subjects were fifth-grade students in Natural and Social Sciences (IPAS). The results showed that the Circulatory System teaching aids developed from plastic waste (upcycling) met the criteria of high feasibility and practicality (Expert Validity: >90%, Teacher/Student Practicality: >90%). The effectiveness test results demonstrated that the implementation of this upcycling media significantly improved students' cognitive understanding, as demonstrated by the high N-Gain score. Furthermore, the active use of plastic waste in the media creation process proved effective in fostering ecological awareness and students' reuse skills. Therefore, this upcycling media is recommended as an effective, contextual, and sustainable pedagogical solution for achieving the goals of IPAS education.